Profil pendidikan karakter dalam pembelajaran pendidikan pancasila dan kewarganegaraan (ppkn) materi simbol-simbol pancasila kelas IV di SD - Gilang Pratana Utama Putra; Hasan Mahfud; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2021)
This research was conducted to determine the profile of the implementation of character education in the PPKn learning material for grade IV Pancasila symbols. The research conducted at SD N Setono Surakarta in 2020/2021 is a descriptive qualitative research. Sources of data came from grade IV students and teachers. Sampling using purposive sampling technique with data collection techniques interviews, questionnaires, and documents. Data validation used source triangulation. The data analysis technique used the analysis of Miles and Huberman. This research stage is the pre-field stage, the fieldwork stage, and the data analysis stage. The result of the research is that the teacher has implemented and provided teaching on character education, especially religion, hard work, discipline, and honesty in learning the PPKn material on the symbols of Pancasila. The implementation of character education is still not optimal because it has several obstacles but the teacher has tried to solve these problems.